Isolation of Klebsiella pneumoniae Phage vB_KpnS_MK54 and Pathological Assessment of Endolysin in the Treatment of Pneumonia Mice Model - Lu, Biao; Yao, Xueping; Han, Guangli; Luo, Zidan; Zhang, Jieru; Yong, Kang; Wang, Yin; Luo, Yan; Yang, Zexiao; Ren, Meishen; Cao, Suizhong (Frontiers in Microbiology, 2022)
With the improper use of antibiotics, an increasing number of multidrug-resistant bacteria have been reported worldwide, posing challenges for disease treatment. Klebsiella pneumoniae is an important zoonotic pathogen that colonises the respiratory tract. Endolysin therapy has emerged with the development of phages. In this study, a lytic phage vB_KpnS_MK54 was isolated from the drinking water of a forest musk deer (FMD) farm in Sichuan Province, the phage was the first phage obtained from FMD. The primary biological characteristics were determined, and whole-genome sequencing analysis was performed. The phage belongs to the family Siphoviridae, and MK54 is highly specific for lytic host bacteria and is moderately adaptable to different environments. Whole-genome sequencing results showed that the phage genome size was 46,218 bp. There were 80 coding DNA sequences (CDSs) in total, 32 of which had known functions. The last CDS is the phage endolysin LysG24. A new peptide-modified endolysin (LysCA) was constituted by connecting the cecropin A peptide residues with LysG24 to investigate the antibacterial activities of both LysG24 and LysCA. The results showed that the lytic profile of LysG24 and LysCA was wider than that of phage MK54. For in vitro tests, both endolysins destroyed 99% of the host bacteria within 6 hours. The lysing ability and environmental adaptability of LysCA were significantly stronger than those of LysG24. For in vivo tests, LysG24 and LysCA exhibited therapeutic effects in a mouse model of pneumonia wherewith the mice were infected with K. pneumoniae (LPKP), wherein both LysG24 and LysCA can effectively reduce the pulmonary inflammatory response. The LPKP bacterial load in the treatment group was significantly lower than that in the bacterial group, among which LysCA displayed a more obvious therapeutic effect. Furthermore, the safety test showed that the endolysins had no toxic effects in mice. In general, both LysG24 and LysCA showed excellent antibacterial activity in vivo and in vitro, with high safety and strong adaptability to the environment, manifesting their latent potential as new antimicrobial agents.